2015
DOI: 10.1139/cjfr-2014-0247
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Picea abies clones with a homokaryotic isolate of Heterobasidion parviporum under field conditions

Abstract: Heterobasidion parviporum Niemelä & Korhonen is responsible for the majority of decay in conifers in northern Europe, which causes severe economic losses. In nature, heterokaryotic isolates of H. parviporum cause infection in Norway spruce (Picea abies (L.) Karst.). However, little is known on whether homokaryons of H. parviporum can infect trees under field conditions. In this study, 40-year-old clonal Norway spruce stems and roots were inoculated with a homokaryotic isolate of H. parviporum under field condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
2
9
1
Order By: Relevance
“…Inoculation of homokaryotic H. parviporum isolates on Norway spruce seedlings further confirmed that heterokaryosis is not absolutely required for the pathogenicity of H. parviporum homokaryons as previously observed [ 70 , 71 ]. We then examined other phenotypic traits i.e.…”
Section: Discussionsupporting
confidence: 85%
“…Inoculation of homokaryotic H. parviporum isolates on Norway spruce seedlings further confirmed that heterokaryosis is not absolutely required for the pathogenicity of H. parviporum homokaryons as previously observed [ 70 , 71 ]. We then examined other phenotypic traits i.e.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the fact that field studies on root disease in natural forest ecosystem require more time than greenhouse studies (Swedjemark and Stenlid 1996), artificial inoculations have been applied successfully in the field experiments to examine tree susceptibility to Heterobasidion infection (Swedjemark and Karlsson 2004;Karlsson et al 2008;Danielsson et al 2011;Keriö et al 2014). Although artificial inoculation followed by sampling of lesion areas is commonly done, relying solely on destructive inoculation to screen for resistant genotypes poses a technical and logistical challenge, which may be impractical for large-scale screening of novel biomarkers for durable resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The inoculation method used ( Fig. 1) was similar as previously described (Keriö et al 2014;Mukrimin et al 2018). The stem surface was sterilized with 70% ethanol followed by making a hole with a 70% ethanol-sterilized puncher (10-mm diameter) through the tree bark to remove the rhytidome, phellem, and cambium.…”
Section: Inoculations Sample Harvesting and Measurementmentioning
confidence: 99%
“…However, a combination of biotic and abiotic factors pose a threat to sustainable timber supply from Norway spruce plantations (Lindroth and St. Clair, 2013 ; Oliva et al, 2013 ; Robert et al, 2013 ; Lind et al, 2014 ; Wang et al, 2015 ). Among microbial pathogens of Norway spruce, necrotrophic fungi of the Heterobasidion annosum species complex occupy an outstanding position due to their devastating effect on commercial plantations (Keriö et al, 2014 ). Members of this species complex are causative agents of root and butt rot of conifer trees throughout the boreal and temperate zones of Northern hemisphere (Abu et al, 2004 ; Asiegbu et al, 2005a ; Garbelotto and Gonthier, 2013 ; Gunulf et al, 2013 ; Skrøppa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%